Double Positive CD4+CD8+ T Cells Are Enriched in Urological Cancers and Favor T Helper-2 Polarization - Bohner, Perrine; Chevalier, Mathieu F.; Cesson, Valérie; Rodrigues-Dias, Sonia-Christina; Dartiguenave, Florence; Burruni, Rodolfo; Tawadros, Thomas; Valerio, Massimo; Lucca, Ilaria; Nardelli-Haefliger, Denise; Jichlinski, Patrice; Derré, Laurent (Frontiers in Immunology, 2019)
The immune system plays a central role in cancer development, showing both anti-tumor and pro-tumor activities depending on the immune cell subsets and the disease context. While CD8 T cells are associated with a favorable outcome in most cancers, only T helper type 1 (Th1) CD4 T cells play a protective role, in contrast to Th2 CD4 T cells. Double positive (DP) CD4+CD8+ T cells remain understudied, although they were already described in human cancers, with conflicting data regarding their role. Here, we quantified and phenotypically/functionally characterized DP T cells in blood from urological cancer patients. We analyzed blood leukocytes of 24 healthy donors (HD) and 114 patients with urological cancers, including bladder (n=54), prostate (n=31) and kidney (n=29) cancer patients using 10-color flow cytometry. As compared to HD, levels of circulating DP T cells were elevated in all urological cancer patients, which could be attributed to increased frequencies of both CD4highCD8low and CD4+CD8high DP T-cell subsets. Of note, most CD4highCD8low DP T cells show a CD8αα phenotype, whereas CD4+CD8high cells express both CD8α and CD8β subunits. Functional properties were investigated using ex-vivo generated DP T-cell clones. DP T cells from patients were skewed toward an effector memory phenotype, along with enhanced Th2 cytokine production. Interestingly, both CD8αα and CD8αβ DP T cells were able to trigger Th2 polarization of naïve CD4 T cells, while restraining Th1 induction. Thus, these data highlight a previously unrecognized immunoregulatory mechanism involving DP CD4+CD8+ T cells in urological cancers.